Rancang Bangun Sistem Informasi Pemesanan Air Galon Berbasis Web Menggunakan Metode RAD - Muhammad Rizal; Galet Guntoro Setiaji; Badroe Zaman (TIN: Terapan Informatika Nusantara, 2026)
The utilization of digital technology has become an essential aspect of improving business management effectiveness, including in the water refill depot sector. At Air Tirta Kencana Depot in Demak Regency, the ordering process and transaction recording are still carried out manually, resulting in slower data processing, an increased risk of recording errors, and customer service that has not been performed optimally. This study aimed to develop a website-based water gallon ordering system by applying the Rapid Application Development (RAD) approach. Research data were collected through observation, interviews, and literature studies. System testing was conducted involving 13 respondents to evaluate system functionality and usability using Black Box Testing and User Acceptance Testing. The developed system was equipped with integrated features for customer data management, transaction ordering, and sales information within a single platform. The integration of these features facilitated ordering, recording, and transaction monitoring processes in a more organized manner according to the operational needs of the depot. In addition, the system enabled users to access order information more quickly and systematically. Based on the testing results, the web-based information system was able to support transaction recording processes to become faster, more organized, and easier to manage. Furthermore, the system achieved a testing success rate of 80% and assisted in monitoring orders and transactions more accurately. The contribution of this research lies in the development of an integrated ordering and transaction management system within a single platform, enabling depot operational processes to be monitored in a more structured manner. Based on these findings, the system also supports more effective business decision-making and helps improve the overall operational quality of the water depot.